PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO - Sarumaha, Jhon Feliks (Universitas Nias Raya, 2024)
The objective of this study is to assess the impact of brand image and product quality on the purchasing choices of Oppo Smartphones among students at the Faculty of Economics and Business, Nias Raya University. The research is conducted at the Faculty of Economics and Business, Nias Raya University. This research is quantitative and has an associative aspect. The data utilized is quantitative in nature, and the source of the data is primary. The research utilized a population and sample size of 50 individuals. The employed methodology is multiple regression analysis. The findings of this study indicate that brand image (X1) has a favorable and statistically significant influence on purchasing decisions, although product quality (X2) also exerts a positive and statistically significant impact on decisions. The purchasing decisions are influenced by both the brand image and the quality of the goods. The recommendations in this study are as follows: 1) The Oppo Smartphone company should focus on preserving its brand image and enhancing the reputation of Oppo Smartphones to stimulate consumer buying behavior. 2) The company must produce high-quality Oppo Smartphone products that are comparable to those available to consumers in order to attract customers and encourage them to acquire Oppo Smartphone products.